Design Of Automation Inspection System Using Cluster Identification Method Based On Leather Shoes ColourAt Venamon Corporation - Fauzan Ghifari; Haris Rachmat; Denny Sukma Eka Atmaja (eProceedings of Engineering, 2015)
Abstract 1,2,3 Prodi S1 Teknik Industri, Fakultas Teknik, Universitas TelkomVisual identification using the human eye as the primary senses has limitations. The limitations of the eye as a visual identification are the factor of fatigue and lack of endurance. This drawback occurs when done a visual identification of products on the production line or for other identification process. Therefore, man developed a visual identification automation system which is called vision system. Indonesia is growing rapidly in the textile industry. Especially the textile industry uses a wide variety of basic materials of leather. Therefore, we need a system utilizing automated vision system for identifying the type and quality of the leather. Vision System using MATLAB language can be applied in a variety of automated systems, which one of them is for processing of basic materials in various products such as leather shoes, handbags, and wallets. Textile industry nowadays, identified clusters leather still using manual methods, which causes much human error on its application. Vision System work begins with the user input the samples to the conveyor, then the camera will capture the leathers material through a graphical user interface in MATLAB assisted with stable lighting. Then the sampling results will be processed by MATLAB that the result will be stored in the database which is actuated by pneumatic system controlled by a programmable logic controller. Keywords— Vision System, Industrial Automation, Cluster Identification, Programmable Logic controller, RGB